HUBUNGAN POLA MAKAN DENGAN RISIKO HIPERTENSI DALAM KEHAMILANPADA IBU HAMIL TRIMESTER III DI PUSKESMAS REJOSARI PEKANBARU TAHUN 2017 - Nelfi Sarlis (Ensiklopedia of Journal, 2018)
Hypertension In Pregnancy (HDK) is one of the vascular disorders that occur during pregnancy or at the time of postpartum mother. It is said pregnancy hypertension when blood pressure ? 140/90 mmHg caused by pregnancy itself, has the potential to cause serious disorders in pregnancy. This study aims to determine the relationship of diet with risk of hypertension in pregnancy in third trimester pregnant women at Rejosari Puskesmas Pekanbaru Year 2017. This research method using this type of research is quantitative with cross sectional design. This research was conducted at Puskesmas Rejosari Pekanbaru in May 2017. Sampling technique using consecutive sampling, population in this study amounted to 2304 people and the sample amounted to 96 people. Data collection using primary data using questionnaire. Data processing done by SPSS include editing, coding, scoring and tabulating. The analysis used is univariate and bivariate. Result of research got majority of responden have good diet as much 58 people (60,4%) and do not risk pregnancy hypertension counted 75 person (78,1%). Based on the result of bivariate analysis, there is correlation between eating pattern and hypertension in Puskesmas Rejosari Pekanbaru Year 2017 with Pvalue that is 0,009